PENGARUH LILIN AROMATERAPI MINYAK LAVENDER (LAVANDULA ANGUSTIFOLIA) TERHADAP KONSENTRASI BELAJAR PADA SISWA MADRASAH TSANAWIYAH AL-WASHLIYAH PASAR MIRING DI DESA PASAR MIRING - anggraeni, Ratih; ., Muriati; Pranata, Chandra (Jurnal FARMASIMED (JFM), 2021)
Aromatherapy is an ancient healing process that uses pure aromatherapy plant extracts aimed at improving the health and well-being of the body, mind and spirit. Lavender contains linalil acetate and linalool. Linalil acetate and linalool have no harmful side effects on health. This substance is antibacterial, fungicidal, viriside, parasiticidal and vermifugal and has neurotonic and uterotonic action. This study aims to determine the effect of lavender oil (Lavandula angustifolia) aromatherapy candles on increasing the concentration of student learning at the Madrasah Tsanawiyah Al-Wasliyah Pasar Miring in Desa Pasar Miring . The study used a quasi-pretest-posttest experimental method for 30 randomly selected students. The instrument in this study used the Army Alpha Test with data analysis using Paired T-Test. Hypothesis testing using Paired T-Test showed p value = 0.026<0.05 (p <0.05). It can be concluded that there is an influence of lavender oil aromatherapy candles on increasing the concentration of student learning in Madrasah Tsanawiyah Al-Wasliyah Pasar Miring in Desa Pasar Miring